Holocene evolution of the shelf mud deposits in the north-western South China Sea - Li, Gang; Miao, Li; Yan, Wen (Frontiers in Marine Science, 2022)
Marine mud deposits contain rich information on past interactions between riverine sediment fluxes and marine processes. Massive mud deposits attached to a major river from South China, the Pearl River, are distributed on the north-western shelf of the South China Sea. This study examines the evolution history using cores penetrating through Holocene strata and deciphers its response to the river system, sea-level change, monsoon variations, human activities, etc. Geochemical and sedimentological data constrained by robust radiocarbon data show the difference in the evolution of mud deposits in shallow waters and on the middle shelf. Muddy wedges in shallow waters along the coast have formed since 7 ka BP, when modern current systems were established during the middle Holocene sea-level highstand. However, wide-spread muddy deposits in the middle shelf initiated after 3 ka BP which are associated with enhanced sediment fluxes and strengthened winter monsoon. Human activities on recent millennia have play a significant role in influencing the mud deposition on the north-west shelf of the South China Sea, as evidenced by the enrichment of heavy metals in marine sediments.